ANALISIS MODEL PEREMAJAAN PERKEBUNAN KELAPA SAWIT POLA PLASMA DI DESA MERANTI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN PROVINSI RIAU - Pratiwi Manurung, Lamtiur; Hutabarat, Sakti; Kaswarina, Shorea (SOROT, 2015)
Riau province is the largerst area of oil palm plantation in Indonesia. Oil palm has been cultivated commercially since 1970s by national enterprises and 1980s by smallholders. In the last ten years, production of the majority of the oil palm trees start declining. More than half of the area have to be replanted. However, the growers, particularly smallholders often delay the replanting activities due to various reasons such as access to funds, plant materials, and other inputs. The objective of this study is to evaluate the feasibility of replanting models of oil palm scheme smallholders using investment criteria analysis (Net Present Value, Internal Rate of Return, and Net Benefit Cost Ratio). Then, study on alternative replanting models was made to find the most suitable model for the scheme smallholders. The result shows that most of the smallholders have implemented best practices in their oil palm plantation. However, since the age of the trees are more than 26 years old, the oil palm production continuous to decline. An assessment on three replanting models shows that all the models are feasible to the smallholders. Nevertheless, the intercropping model is the most suitable to the smallholders.